2005
DOI: 10.1039/b419474h
|View full text |Cite
|
Sign up to set email alerts
|

A 2D honeycomb-shaped network based on a starburst cluster: [Ag43-Cl)(PPh2(CH2)2PPh2)1.5{S2P(OR)2}3] (R = Et, Pri)

Abstract: The first 2D metal-organic framework utilizing PPh2(CH2)2PPh2 (dppe) units as the linkers and tetranuclear silver clusters, [Ag4(micro3)-Cl){S2P(OR)2}3], as the network nodes in the formation of the honeycomb-shaped layer structure is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 25 publications
(9 reference statements)
1
16
0
Order By: Relevance
“…[24] In [Ag 2 Cl 4 ] 2À , which contains trigonal-planar Ag + ions, Ag À Cl distances range from 2.359(2) to 2.809(2) , [25] and in a dinuclear mixed N,Pligand complex with AgA C H T U N G T R E N N U N G (m-Cl)Ag bridges and tetrahedral Ag + coordination geometries, these distances are between 2.601(9) and 2.701(4) , [26] very much as in an Ag 4 A C H T U N G T R E N N U N G (m 3 -Cl) cluster. [27] Typical AgÀCl bond lengths in mixed PtA C H T U N G T R E N N U N G (m-Cl)Ag complexes, as described by Usón, ForniØs, and co-workers, are in the order of 2.41(1)-2.56(1) . [18,28] The Ag À Cl bond distance in compound 12 (2.459 (3) ) is in the range of those in the latter compounds, even though the chlorido ligand is terminal, rather than bridging.…”
Section: H T U N G T R E N N U N G (Nh 2 ) 2 (Oh)-a C H T U N G T Rmentioning
confidence: 96%
“…[24] In [Ag 2 Cl 4 ] 2À , which contains trigonal-planar Ag + ions, Ag À Cl distances range from 2.359(2) to 2.809(2) , [25] and in a dinuclear mixed N,Pligand complex with AgA C H T U N G T R E N N U N G (m-Cl)Ag bridges and tetrahedral Ag + coordination geometries, these distances are between 2.601(9) and 2.701(4) , [26] very much as in an Ag 4 A C H T U N G T R E N N U N G (m 3 -Cl) cluster. [27] Typical AgÀCl bond lengths in mixed PtA C H T U N G T R E N N U N G (m-Cl)Ag complexes, as described by Usón, ForniØs, and co-workers, are in the order of 2.41(1)-2.56(1) . [18,28] The Ag À Cl bond distance in compound 12 (2.459 (3) ) is in the range of those in the latter compounds, even though the chlorido ligand is terminal, rather than bridging.…”
Section: H T U N G T R E N N U N G (Nh 2 ) 2 (Oh)-a C H T U N G T Rmentioning
confidence: 96%
“…The principle of weak interactions (e.g., hydrogen bonding or weak electrostatic interaction between chalcogenide atoms and heavier alkali metal atoms), however, has not been extensively exploited in the area of phosphorus-chalcogenides. Instead synthetic efforts continue to concentrate on metal complexes with ligands designed by formally replacing O atoms in phosphate ions with OR, SR, S, Se, OSe [6][7][8][9]. In previous work it was shown that reactions of metal salts MX (X = alkoxide, thiolate, carboxylate) with reagents of the type [RP(E)(l-E)] 2 (R = organic group, E = S, Se [10,11]) and binary phosphorus sulfides offer an alternative route to complexes containing P/S-or P/Se-based anionic ligands [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Simple stirring of Ag(I), dppm and dtp sources in 1:1:1 ratio at RT in acetonitrile produces [Ag 4 (dppm) 2 [Ag 4 (l 3 -Cl)(dppe) 1.5 {S 2 P(OEt) 2 } 3 ] 1 (6a) in 63% and 6% yield, respectively [1]. We have recently isolated 5a', a polymorph of 5a, when single crystal were grown from acetone instead of dichloromethane.…”
Section: Synthesismentioning
confidence: 99%
“…Structural characterization reveal the formation of tetranuclear, [ [Ag 4 (dppm) 2 4 (l 3 -Cl)(dppe) 1.5 {S 2 P(OR) 2 } 3 ] 1 (R = Et, 6a; i Pr, 6b)] polymers are obtained in the presence of dppe and dppb with longer spacer in the diphosphine backbone. A part of this work has been communicated earlier containing the description of 5a, 5b, 6a and 6b [1]. The dtp ligands exhibited various bonding modes in the complexes 1-8 as depicted in Chart 1.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation